2023
DOI: 10.1152/ajplung.00058.2023
|View full text |Cite
|
Sign up to set email alerts
|

Baseline reticular basement membrane morphology is related to subsequent spirometry deterioration in pediatric chronic airway inflammation: a follow-up study

Abstract: Reticular basement membrane (RBM) thickening may occur in children with allergic bronchial asthma (BA), cystic fibrosis (CF), and primary ciliary dyskinesia (PCD). Its functional consequences remain unknown. We investigated the relationship between baseline RBM thickness and subsequent spirometry. In our cohort follow-up study, patients aged 3-18 years with BA, CF, and PCD and controls underwent baseline lung clearance index (LCI) measurement, spirometry, and endobronchial biopsy sampling. Total RBM and collag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…It is known that reticular basement membrane thickening can be present in allergic bronchial asthma and in other bronchial illnesses, such as primary ciliary dyskinesia and cystic fibrosis. In a study of multiple regression models, Koucký et al showed that changes in reticular basement membrane morphology resulted in diminished lung function by evaluating the z-scores of FEV1 and the FEV1/FVC ratio [ 82 ].…”
Section: Biomarkersmentioning
confidence: 99%

Early Prediction of Asthma

Romero-Tapia,
Becerril-Negrete,
Castro-Rodriguez
et al. 2023
JCM
“…It is known that reticular basement membrane thickening can be present in allergic bronchial asthma and in other bronchial illnesses, such as primary ciliary dyskinesia and cystic fibrosis. In a study of multiple regression models, Koucký et al showed that changes in reticular basement membrane morphology resulted in diminished lung function by evaluating the z-scores of FEV1 and the FEV1/FVC ratio [ 82 ].…”
Section: Biomarkersmentioning
confidence: 99%

Early Prediction of Asthma

Romero-Tapia,
Becerril-Negrete,
Castro-Rodriguez
et al. 2023
JCM